2009
DOI: 10.1021/jp9017844
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Thioether Molecular Rotors: Effects of Surface Interactions and Chain Flexibility

Abstract: Recent single-molecule experiments indicated that thioethers (dialkyl sulfides) on gold surfaces act as thermallyor mechanically activated molecular rotors, although the mechanisms for these phenomena are not yet clearly understood. Here we present theoretical and experimental investigations of the rotational dynamics of these thioether molecules. Single-molecule studies utilizing low-temperature scanning tunneling microscopy allowed us to determine rotational rates and activation energies for the rotation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(80 citation statements)
references
References 46 publications
2
74
2
2
Order By: Relevance
“…As reported in previous work by this group, isolated DBS molecules behaved as molecular rotors on Au{111}. [22][23][24]42,43 The central sulfur atom acted as an anchor and the alkyl tails rotated between three high symmetry directions; at 78 K the rotation was significantly faster than the STM imaging rate (∼2 min per image), and the molecules appeared hexagonal in shape, as depicted in Figure 2A. Furthermore, the molecules rotated at a rate significantly greater than that of translational motion, as evidenced by STM movies acquired at 78 K, in which rotating molecules did not diffuse more than a few lattice spacings throughout the movie taken over several hours (see Supporting Information).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…As reported in previous work by this group, isolated DBS molecules behaved as molecular rotors on Au{111}. [22][23][24]42,43 The central sulfur atom acted as an anchor and the alkyl tails rotated between three high symmetry directions; at 78 K the rotation was significantly faster than the STM imaging rate (∼2 min per image), and the molecules appeared hexagonal in shape, as depicted in Figure 2A. Furthermore, the molecules rotated at a rate significantly greater than that of translational motion, as evidenced by STM movies acquired at 78 K, in which rotating molecules did not diffuse more than a few lattice spacings throughout the movie taken over several hours (see Supporting Information).…”
Section: Resultssupporting
confidence: 73%
“…15, 16 More recent studies, however, have conclusively shown that thioethers with tails up to 18 carbons in length adsorb with their alkyl tails parallel to the surface. [17][18][19][20][21][22][23][24] As such, adjusting side chain length may enable control over lateral spacing. It has also been debated whether thioether species dissociate upon adsorption via cleavage of a S-C bond, 25 but it is now accepted that these species adsorb intact.…”
Section: Introductionmentioning
confidence: 99%
“…The molecule ends in conformation f2cg at I Set ¼ 0:5 nA. Recent publications have shown that a configurational change of a molecule on a metal surface can be imaged by STM [25,26] and that a rotation of molecules in an increasing electric field can be monitored by a sequence of STM images [27]. Consequently, the change of electronic properties related to different adsorption geometries can be monitored by STS, as reported in this work.…”
Section: Prl 105 066801 (2010) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 61%
“…The surface was represented as a slab of 1067 gold atoms organized in 3 layers (surface plane 111) and their 2D replicas, thus effectively leading to quasi-infinite representation of the surface, similar to what was utilized in earlier studies 31. Two different surfaces Au (111) and Au (100) have been used in our calculations.…”
Section: Theoretical Calculationsmentioning
confidence: 99%